MENGATASI PRASANGKA DAN KONFLIK SOSIAL MELALUI PERAYAAN-PERAYAAN BERASAMA DALAM KONTEKS KOTA AMBON YANG MULTIKULTUR - Hateyong, Elizabeth; Refo, Ignasius Samson Sudirman; Seralarat, Kornelis (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2020)
Prejudice and conflict are multicultural challenges in many urban areas including the city of Ambon. Even the challenges of Ambon city are getting heavier given the legacy of a religiously nuanced horizontal conflict that occurred several years ago. Now Ambon looks calm and peaceful. Even many parties have declared Ambon as a harmony community. However, other parties are still doubtful and consider peace in Ambon only at the ceremonial level. With a qualitative approach, field study and literature study, this research explains that religious activities and celebration that have involved so many people from different religious communities have shown how progress in harmony and peace in Ambon city and Moluccas.